Rasch analysis on individual cognitive styles for museum learning performances - Alwi, Asmidah (2012)
The advantages offered by the web-based environment have successfully convinced museums around the world to employ the technology in enriching their visitors’ learning experiences.However, the design and development of such environment in presenting the museum exhibits is challenging due to the complexities of human-computer interaction. The diverse profiles of museum visitors also add to the dilemma in designing effective museum leaning experiences for all.This paper addresses the issue by focusing on the effects between media representation formats and individual cognitive preferences.The data collected utilizing a quasi-experimental design was then analyzed using Rasch Model. The findings reveal that cognitive styles do have an effect on the learning performance thus should be consider during the design process of the learning environment.